The Impact of Urban-Rural Income Inequality on Environmental Quality in China. (21st April 2022) - Xiao, De; Yu, Fan; Yang, Hong
Abstract : As the per capita income level increases, both environmental quality and income inequality will change significantly, which arouses people's attention on the relationship between income inequality and environmental quality. Based on mathematical derivations, we first prove that when the relationship between per capita income and environmental pollution is nonlinear, and environmental pollution is not only related to per capita income, but also, among other potential determinants, to income inequality. Then, we use the two-way fixed estimator to estimate the impact of income inequality on environmental quality by decomposing the Stochastic Impacts by Regression on Population, Affluence, and Technology (STIRPAT) model. (1) The impact of income inequality on environmental pollution is significantly positive, that is, as the income gap widens, industrial pollutant emissions, carbon dioxide emissions, and PM2.5 in the air will increase; (2) there is an "Inverted U-shaped" impact relationship between income inequality and environmental quality, that is, environmental pollution increases first and then decreases with the increase of per capita GDP; (3) per capita income is the intermediate variable between income inequality and environmental quality. The relationship between income inequality and environmental quality should be fully considered when formulating relevant policies. The government should adopt differentiated environmental policies targeted at low-and-high income groups to achieve a win-win situation of economic growth and environmental protection.